Pengembangan Sumur Bor Air Tanah di Pondok Tahfidzul Qur’an Miftahul Jannah Putri Pamanjengan, Moncongloe - Maros - Muhammad - Ramli; Purwanto -; Aryanti Virtanti Anas; Rini Novrianti Sutadrjo Tui; Nirmana Fiqra Qaidahiyani; Asta Arjunoarwan Hatta (Faculty of Engineering UNHAS, 2022)
The partner of this community service activity is Islamic Boarding Schoo of Tahfidzul Qur'an of Miftahul Jannah Putri in Pamanjengan, Moncongloe, Maros Regency. This boarding school guides 10 students from underprivileged families. The partner's main problem is the difficulty in meeting water needs for daily needs because there is no clean water service available through the network of Regional Drinking Water Companies and limited groundwater production from existing bore wells. Therefore, the boarding school manager and students tries to get ground water by developing the addition of groundwater wells as seen from the results of the pre-test. This boarding school has an area of ​​800 m2 making it possible to develop a better groundwater borehole. However, there are concerns about its success because several well drillings that have been carried out in its vicinity have not succeeded in obtaining water of the quality and quantity as expected. Therefore, this groundwater well development activity is carried out in stages based on a groundwater science approach which includes the stages of surface mapping, geoelectrical measurement, groundwater drilling, well construction and pumping. Drilling was carried out to a depth of 60 meters. The drilled well was pumped at a flow rate of 0.40 liters/second (1,440 liters/hour) and reached steady state at a water table drop of 1.60 meters. Thus, this community service activity was declared successful in accordance with the output target with the availability of groundwater production wells of good quality and sufficient quantity to meet the needs of the boarding school. The post-test results show that the existence of the well gives confidence that water needs will be met with additional groundwater drilled wells from this activity.